ASSOCIATION BETWEEN ADULT TUBERCULOSIS TREATMENT STATUS WITH CHILDREN TUBERCULOSIS STATUS WHO HAD HOUSEHOLD CONTACT - Agnes Emanuella; Moh. Syarofil Anam; Nahwa Arkhaesi; Dodik Pramono (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Bacground: Tuberculosis (TB) is one of the ten types of diseases that cause the quite high death rate in the world. Indonesia is ranked number three in TB cases. Tuberculosis can spread from adult tuberculosis patients to others including children who have a history of household contact. Adult TB patients who have been diagnosed immediately receive treatment to cure and reduce transmission. Tuberculosis treatment is divided into intensive phase, advanced phase and successful treatment. Aim: This study aims to analyze the relationship between treatment status of tuberculosis on adult who contact with tuberculosis status on children in the houshold. Methods: This study was an observational analytic study with a cross sectional study. The subjects of this study were 35 adult TB patients who were in contact with 58 children aged 0-18 years. Data collection was carried out at RSUP Kariadi and four puskesmas in Semarang from September 2019 to October 2019. Children tuberculosis status was classified as being TB exposure, TB infection and TB disease based on tuberculin tests and clinical symptoms. Statistical tests using the Chi-Square and Fisher Exact hypothesis tests. Results: Based on the results of statistical analysis, there was no significant relationship between the status of tuberculosis treatment on adult (p = 0.848) with status of tuberculosis for children that are in household contact. Conclusion: The status of tuberculosis treatment on adult has no statistical relationship with the status of tuberculosis for children in household contact.